Piqray – basic questions at the start: whom to test? whom to treat? how to treat? Event review of the satellite symposium. RUSSCO Big Conference «Breast Cancer» (online). January 29th, 2021 - Editorial Board (IP Habib O.N., 2021)
A Satellite Symposium of Novartis Pharma was held on January 29th, 2021, within the framework of the RUSSCO Big Conference Breast Cancer. It was dedicated to the diagnostics and treatment of patients with hormone-dependent HER2-negative advanced breast cancer (HR+ HER2- aBC) with a PIK3CA mutation using target drug Piqray (alpelisib). Experts-oncologists discussed the diagnostics of the PIK3CA mutation, data from clinical studies of alpelisib, characteristics of patients who may benefit from the alpelisib, prevention and control of adverse events that may develop during therapy with alpelisib. For planning anticancer therapy using alpelisib in combination with fulvestrant, all patients with HR+ HER2- aBC should be tested for PIK3CA mutation at the first signs of a metastatic process. Data from clinical trials demonstrate that this combination provides approximately 2-fold increase in median progression free survival compared to a placebo + fulvestrant combination. Alpelisib can be prescribed to patients with HR+ HER2- aBC with a PIK3CA mutation after progression on endocrine therapy, in a combined mode. The main adverse events hyperglycemia and rash are associated with the mechanism of alpelisib action, and are predictable and manageable.